Hedgehog Signalling in the Embryonic Mouse Thymus - Barbarulo, Alessandro (J Dev Biol, 2016)
T cells develop in the thymus, which provides an essential environment for T cell fate specification, and for the differentiation of multipotent progenitor cells into major histocompatibility complex (MHC)-restricted, non-autoreactive T cells. Here we review the role of the Hedgehog signalling pathway in T cell development, thymic epithelial cell (TEC) development, and thymocyte–TEC cross-talk in the embryonic mouse thymus during the last week of gestation.